Caracterização de um vermicomposto com diferentes tempos de bioconversão - Ramos, Rodrigo Ferraz (2021)
Vermicomposting is an environmental-friendly process of biotransformation of organic waste into useful products. The aim of the study was to evaluate the relationship between vermicomposting time and changes in biological, physical, and chemical attributes during bovine manure vermicomposting. Pots (vermireactors) containing 4 kg of cattle manure were inoculated with Eisenia andrei at a population density equivalent to 5,000 adult earthworms m-2. Changes in the physical-chemical and biological parameters were evaluated at 15, 30, 45, 60 and 120 days of vermicomposting and compared with the contents found in cattle manure. The initial phase of vermicomposting (0-45 days) was characterized by high basal respiration while the maturation phase (45-120 days) was characterized by high earthworm density and biomass and concentration of nutrients in the vermicompost. During the 120 days, there was a decrease in microbial activity (56%), vermicompost mass (35%), organic matter (10%), total organic carbon (13%), total organic nitrogen (6.0% ), the C / N ratio (8.0%) and the C / P ratio (45%). In contrast, there were increases in ash content (53%), electrical conductivity (23%), K (18%), P (57%), Ca (62%), Mg (54%), Cu (37%) , Zn (51%), NO2- + NO3- (39%), NH4+ (14%), total mineral N (26%), dissolved organic C / N ratio (83%) and bulk density (34%). Vermicomposting also resulted in changes in the degree of aromaticity of the dissolved organic matter. There was a great population growth of earthworms in the final stage of vermicomposting, reaching values of 34,000 earthworms m-2 and 87,000 cocoons m-2. We have demonstrated that 30 days of vermicomposting is sufficient to obtain a quality organic fertilizer, however it is necessary 120 days to obtain satisfactory results in the production of earthworms.